ELECTROENCEPHALOGRAPHIC FEATURES OF CHILDHOOD EPILEPSY (ResearchJet Journal of Analysis and Inventions, 2021)
Electroencephalography was performed for 105 children with epilepsy.  The features of EEG patterns in generalized and partial seizures in children of various age categories were revealed